2006
DOI: 10.1002/jts.20138
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus among Cambodian refugees: Relationship to PTSD severity

Abstract: Consecutive Cambodian refugees attending a psychiatric clinic were assessed for the presence and severity of current tinnitus (i.e., at least one episode in the last month). Fifty percent (52/104) of surveyed patients had tinnitus. Among the tinnitus patients, posttraumatic stress disorder (PTSD) rates were significantly more elevated than among nontinnitus patients (OR=13.5; 95% CI=5.8 to 39.4), as were Clinician-Administered PTSD Scale (CAPS) scores. In a hierarchical regression among tinnitus patients (n=52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 14 publications
0
69
0
2
Order By: Relevance
“…clinical studies it has been shown that different kinds of stress (such as overall stress, emotional stress, and posttraumatic stress disorder) can intensify sudden hearing loss or tinnitus in humans (Ban and Jin, 2006;Hinton et al, 2006;Fagelson, 2007;Hebert and Lupien, 2007;Al Mana et al, 2008); in general, however, the affected frequency range was not the focus of these studies. Tinnitus occurs mostly as high-pitch, but can also occur as lowpitch, ringing.…”
Section: Discussionmentioning
confidence: 97%
“…clinical studies it has been shown that different kinds of stress (such as overall stress, emotional stress, and posttraumatic stress disorder) can intensify sudden hearing loss or tinnitus in humans (Ban and Jin, 2006;Hinton et al, 2006;Fagelson, 2007;Hebert and Lupien, 2007;Al Mana et al, 2008); in general, however, the affected frequency range was not the focus of these studies. Tinnitus occurs mostly as high-pitch, but can also occur as lowpitch, ringing.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, not every tinnitus patient experiences tinnitus as aversive or bothersome. In addition, many patients describe their phantom pain as triggered by stressful life events (85), and tinnitus is more common in patients suffering posttraumatic stress disorder (86).…”
Section: Phantom Percepts and Memorymentioning
confidence: 99%
“…Many tinnitus patients suffer from insomnia (Cronlein et al, 2016), concentration difficulties (Hallam, McKenna, & Shurlock, 2004; Rossiter, Stevens, & Walker, 2006) or headaches (Langguth et al, 2015). Comorbid mental symptoms of anxiety, depression and post-traumatic stress are common (Fagelson, 2007; Hinton, Chhean, Pich, Hofmann, & Barlow, 2006; McCormack et al, 2015; Pattyn et al, 2016; Zoger, Svedlund, & Holgers, 2006). The economic burden of tinnitus to society is substantial.…”
Section: Introductionmentioning
confidence: 99%